2019
DOI: 10.1002/adma.201803549
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid–Based Activatable Nanomaterials for Stimuli‐Responsive Imaging and Therapeutics: Beyond CD44‐Mediated Drug Delivery

Abstract: There is a rapidly increasing interest in developing stimuli-responsive nanomaterials for treating a variety of diseases. By enabling the activation of function locally at the sites of interest, it is possible to increase therapeutic efficacy significantly while simultaneously reducing adverse side effects. While there are many sophisticated nanomaterials available, they are often highly complex and not easily transferrable to industrial scales and clinical settings. However, nanomaterials based on hyaluronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(121 citation statements)
references
References 169 publications
1
114
0
2
Order By: Relevance
“…Extensive clinical evidence has demonstrated that CD44 and CD168 are overexpressed in several malignant tumors and can be utilized for targeted drug design 25,26 . Hyaluronic acid (HA), a natural polysaccharide composed of N-acetyl-D-glucosamine and D-glucuronic acid, has been rigorously validated as a target of CD44 and CD168 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Extensive clinical evidence has demonstrated that CD44 and CD168 are overexpressed in several malignant tumors and can be utilized for targeted drug design 25,26 . Hyaluronic acid (HA), a natural polysaccharide composed of N-acetyl-D-glucosamine and D-glucuronic acid, has been rigorously validated as a target of CD44 and CD168 27 .…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, several reviews have described the advantages and properties of polymeric nanocarriers [5,7,9,32,62,65,81] as well as HA-based nanosystems [6,79,82,83,84,85,86]. Nonetheless, to the best of our knowledge, none of them have focused on polymeric nanocarriers combining HA and custom-made polymers as major components, as done in this review.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to application in antitumor therapy, nanocarriers based on HA-polymer conjugates or complexes can also be used for several other applications, like rheumatoid arthritis (RA) therapy, delivery of drugs through the brain-blood barrier (BBB), siRNA delivery, sensing bacterial enzymes, imaging, among others [79]. However, as described in this review, only few examples of such applications have been investigated using HA-based polymeric nanocarriers, leaving a large field for future exploration.…”
Section: Ha-based Polymeric Nanocarriers: Challenges and Future Prmentioning
confidence: 99%
“…HA has good biocompatibility and can target the CD44 receptor overexpressed in many types of cancer cells (Toole, 1990 ). When reaching the tumor tissues, hyaluronidase within tumor tissues can degrade HA (Choi et al, 2019 ). Shi et al ( 2016 ) used diiodo-styryl-BODIPY as a PS, and then conjugated HA to prepare hyaluronidas-responsive nanoparticles (named DBHA) as activatable photodynamic theranostics for treating cancer.…”
Section: Tmrns As Targeted Delivery Carriers For Photodynamic Anticanmentioning
confidence: 99%